Concepts in glioma immunotherapy - Platten, Michael; Wick, Wolfgang (Cancer immunology immunotherapy, 2016)
Immunotherapeutic concepts in neurooncology have been developed for many decades but have mainly been hampered by poor definition of relevant antigens and selective measures to target the central nervous system. Independent of the recent remarkable successes in clinical immunooncology with checkpoint inhibitors and vaccines, immunotherapy of brain tumors in general and gliomas in particular has evolved with novel neurooncology-specific concepts over the past years providing new phase 1 approaches of individualized immunotherapy to first phase three clinical trials. These concepts are driven by a high medical need in the absence of approved targeted therapies and refute the classic dogma that the central nervous system is immune-privileged and hence inaccessible to potent antitumor immunity. Instead, measures have been taken to improve the odds for successful immunotherapies, including rational targeting of relevant antigens and integration of immunotherapies into standard of care primary radiochemotherapy to increase the efficacy of antitumor immunity in a meaningful time window. This review highlights concepts and challenges associated with epitope discovery and selection and trial design.
Gesehen am 22.11.2017